2022
DOI: 10.3390/ijms232315081
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Nicotine/Ethanol/Caffeine Mixed Exposure Induces Offspring Rat Dysplasia and Its Potential “GC-IGF1” Programming Mechanism

Abstract: Clinical and animal studies suggest that paternal exposure to adverse environments (bad living habits and chronic stress, etc.) has profound impacts on offspring development; however, the mechanism of paternal disease has not been clarified. In this study, a meta-analysis was first performed to suggest that paternal exposure to nicotine, ethanol, or caffeine is a high-risk factor for adverse pregnancy outcomes. Next, we created a rat model of paternal nicotine/ethanol/caffeine mixed exposure (PME), whereby mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Recently, the rat model, in which the paternal exposure to a combination of nicotine, ethanol, and caffeine demonstrated that such mixed adverse exposure resulted in heightened activity of the hypothalamic pituitary adrenal axis, diminished sperm quality, unfavorable outcomes in pregnancy, abnormal indicators of fetal serum metabolism, and dysfunction in multiple organs in male rats. Notably, the reduced activity of the glucocorticoid-insulin-like growth factor 1 (GC-IGF1) axis may serve as the primary mechanism underlying the developmental and multi-organ dysfunction observed in offspring due to paternal mixed exposure ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the rat model, in which the paternal exposure to a combination of nicotine, ethanol, and caffeine demonstrated that such mixed adverse exposure resulted in heightened activity of the hypothalamic pituitary adrenal axis, diminished sperm quality, unfavorable outcomes in pregnancy, abnormal indicators of fetal serum metabolism, and dysfunction in multiple organs in male rats. Notably, the reduced activity of the glucocorticoid-insulin-like growth factor 1 (GC-IGF1) axis may serve as the primary mechanism underlying the developmental and multi-organ dysfunction observed in offspring due to paternal mixed exposure ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that high levels of glucocorticoids adversely affect the uterus and fetus and inhibit the secretion of pituitary luteinizing hormone, estrogen, and progesterone by the ovary. A lack of progesterone during pregnancy can also be attributed to stress hormone-induced inhibitory effects on female reproductive organs, resulting in the symptoms known as "hypothalamic" amenorrhea and fetal loss [21]. Studies have previously shown that noise exposure stimulates HPA axis activity and increased corticosterone production [22].…”
Section: Discussionmentioning
confidence: 99%